2012
DOI: 10.1371/journal.pone.0035563
|View full text |Cite
|
Sign up to set email alerts
|

Length and Amino Acid Sequence of Peptides Substituted for the 5-HT3A Receptor M3M4 Loop May Affect Channel Expression and Desensitization

Abstract: 5-HT3A receptors are pentameric neurotransmitter-gated ion channels in the Cys-loop receptor family. Each subunit contains an extracellular domain, four transmembrane segments (M1, M2, M3, M4) and a 115 residue intracellular loop between M3 and M4. In contrast, the M3M4 loop in prokaryotic homologues is <15 residues. To investigate the limits of M3M4 loop length and composition on channel function we replaced the 5-HT3A M3M4 loop with two to seven alanine residues (5-HT3A-An = 2–7). Mutants were expressed in X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…2A). The estimated pH value of half-maximal activation (pH 50 ) for ASIC1a was 6.32 Ϯ 0.07 (CI 6.18 -6.48), for ASIC2a was 3.54 Ϯ 0.04 (CI 3.47-3.62), for ASIC1a-F2a was 6.76 Ϯ 0.05 (CI 6.66 -6.86), for ASIC1a-T2a was 6.26 Ϯ 0.06 (CI 6.13-6.39), for ASIC1a-FT2a was 5.23 Ϯ 0.05 (CI 5.14 -5.32), for ASIC2a-T1a was 3.60 Ϯ 0.05 (CI 3.50 -3.69), and for ASIC2a-FT1a was 3.72 Ϯ 0.04 (CI 3.65-3.79) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). The estimated pH value of half-maximal activation (pH 50 ) for ASIC1a was 6.32 Ϯ 0.07 (CI 6.18 -6.48), for ASIC2a was 3.54 Ϯ 0.04 (CI 3.47-3.62), for ASIC1a-F2a was 6.76 Ϯ 0.05 (CI 6.66 -6.86), for ASIC1a-T2a was 6.26 Ϯ 0.06 (CI 6.13-6.39), for ASIC1a-FT2a was 5.23 Ϯ 0.05 (CI 5.14 -5.32), for ASIC2a-T1a was 3.60 Ϯ 0.05 (CI 3.50 -3.69), and for ASIC2a-FT1a was 3.72 Ϯ 0.04 (CI 3.65-3.79) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Assuming all null hypotheses are true, we expect 5% of the comparisons to have uncorrected p values of less than 0.05. The pH of half-maximal activation (pH 50 ) was calculated from normalized pH-evoked peak currents plotted as a function of the pH of activation. Data were fitted to a standard monotonic sigmoid dose-response curve.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown earlier that changes in the M3-M4 loop in eukaryotic CLRs alter expression and desensitization (37)(38)(39), modulate interaction with other proteins (40), and affect the single channel conductance in cation-selective CLRs (41). Alva1-pHCl has an intracellular M3-M4 loop that is 25-30 amino acids long.…”
Section: Discussionmentioning
confidence: 99%
“…McKinnon et al (37) have shown, for the 5-HT3A receptor, that mutants with a polyalanine sequence replacing the native M3-M4 loop were functional, disfavoring a role of charged residues in loss of function. In tAlv-a1-pHCl-AGT, it may be that replacing the M3-M4 loop with the tripeptide AGT restricts the conformational flexibility of the M3 and M4 helices.…”
Section: Discussionmentioning
confidence: 99%
“…The function of this region has been shown to impact channel kinetics and trafficking in other members of the Cys-loop family and provides potential sites for post-translational modifications (Tsetlin et al, 2011;McKinnon et al, 2012). However, it is still unclear how the regions of heterogeneity between isoforms may affect channel activity and expression.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%